Implementation of Smart City Development Policy in Gedebage, Bandung, Indonesia - Darmawansyah, Dimas; Pradoto, Wisnu (The Indonesian Journal of Planning and Development, 2022)
The smart city concept aims to help the people by enhancing information to the community or institutions to carry out activities or anticipate unexpected events to manage resources more efficiently ultimately. Within the smart city field, the Technopolis sub-concept aims for developing a safe and comfortable city life technology supported by accessible, fast, smooth, and productive city management. This project is expected to provide main activities of trade and services, creative and high technology industries, tourism, and transportation. The case study of Gedebage district was chosen because of its power as a fast-growing economic potential by optimizing existing potential, both in the form of physical possibility, resources, and cooperation between the government and the private sector. This type of research is field research, which uses the object of research regarding a symptom or event in community groups. Therefore, this research can also be a case study with a descriptive-quantitative approach. Quantitative analysis shows an actual sign, can be studied epistemologically, and the research that will be carried out aims to find explanations between indicators.  Based on the findings of the analysis and research, it has been determined that the implementation of Bandung city government policies has a significant effect on community participation in planning the Gedebage Sub-region as the new city center of Bandung through the concept of technopolis.